2009
DOI: 10.1007/s11172-009-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dicationic μ-diborolyl triple-decker complexes [CpCo(μ-1,3-C3B2Me5)M(C6H6)]2+ (M = Rh, Ir)

Abstract: Dicationic triple decker complexes [CpCo(μ 1,3 C 3 B 2 Me 5 )M(C 6 H 6 )] 2+ (M = Rh (3), Ir (4)) were synthesized by the reaction of [CpCo(μ C 3 B 2 Me 5 )MBr 2 ] 2 (M = Rh, Ir) with benzene in the presence of AgBF 4 . The structure of 3(BF 4 ) 2 was determined by X ray diffraction analysis.We have earlier synthesized 1 the bromide complexes [CpCo(μ C 3 B 2 Me 5 )MBr 2 ] 2 (M = Rh (1), Ir (2)), which can be used as synthones for triple decker fragments CpCo(C 3 B 2 Me 5 )M. In particular, it was shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…With the aid of computational studies it has been shown that the described complexes and related systems are of interest for molecular electronics16 and for hydrogen storage 17. Herein we describe the synthesis of the first dicationic μ‐diborolyl triple‐decker complexes using bromides [CpCo(μ‐1,3‐C 3 B 2 Me 5 )MBr 2 ] 2 (M = Rh, Ir) as starting materials 18. This methodology is entirely new and is based on the use of specially prepared synthons of triple‐decker complexes, which can be further converted into a wide range of new objects.…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of computational studies it has been shown that the described complexes and related systems are of interest for molecular electronics16 and for hydrogen storage 17. Herein we describe the synthesis of the first dicationic μ‐diborolyl triple‐decker complexes using bromides [CpCo(μ‐1,3‐C 3 B 2 Me 5 )MBr 2 ] 2 (M = Rh, Ir) as starting materials 18. This methodology is entirely new and is based on the use of specially prepared synthons of triple‐decker complexes, which can be further converted into a wide range of new objects.…”
Section: Introductionmentioning
confidence: 99%